STUDY FISHING GROUND IN KAMPAR RIVER PELALAWAN VILLAGE, PELALAWAN DISTRICT, PELALAWAN REGENCY, PROVINCE OF RIAU - Zulkarnain, M.; Yani, Alit Hindri; ', Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in May 2015 in Kampar river Pelalawan village, Pelalawan district, Pelalawan regency, province of Riau. Purpose of this study was to obtain data on environmental parameters become the benchmark fishing grounds and fishing activity there. Environmental parameters measured are temperature, current speed, brightness, depth, acidity (pH) and dissolved oxygen. After doing this research is that the condition of the Kampar river Village Palalawan still quite good and still support for life of organisms that were in it and deserves to fishing activities in these waters.Keyword : fishing ground, environmental parameters, kampar river